Penerapan Sekolah Sehat dan Taat Hukum Pasca Pembelajran Daring di SDN 62 Kabupaten Lebong Provinsi Bengkulu - Bintang Agustina Pratiwi; Rangga Jayanuarto; Weti; Ayu Maharani; Essy Tuwi Susanti (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
The decline in COVID-19 cases supports the re-activation of face-to-face learning. Since learning from home, the school environment has received less attention. In addition, while studying at home, children are more exposed to technology which has a negative impact on narcotics, bullying and hoax news. The purpose of this activity is to create a healthy school again and all students understand the law. Activities are carried out using counseling methods and direct practice in implementing healthy and law-abiding schools. The implementation was carried out for one month at SDN 62 Lebong Regency, Bengkulu Province. The target of this activity is SD 62 students. The results of the activity show a change in student behavior after education, students also take part in creating a healthy school environment, maintaining personal health during the pandemic. In the field of law students know the dangers of narcotics and the penalties for users and drivers. In addition, students also understand that bullying is a criminal act. How not to be influenced by hoax news and not to participate in spreading hoax news. This activity should be carried out regularly so that the school stays healthy and the students obey the law.